129k views
0 votes
Make T the subject of the formula

Make T the subject of the formula-example-1

1 Answer

7 votes

Answer:


t = (3k+6)/(k-2)

Explanation:

Step 1: Multiply both sides by t - 3.


  • kt - 3k = 2t + 6

Step 2: Add -2t to both sides.


  • kt - 3k -2t = 2t + 6 -2t

  • kt-3k -2t = 6

Step 3: Add 3k to both sides.


  • kt-3k-2t+3k=6+3k

  • kt - 2t = 3k + 6

Step 4: Factor our the variable.


  • t(k-2)=3k+6

Step 5: Divide both sides by (k - 2).


  • (t(k-2))/((k-2)) = (3k+6)/(k-2)

  • t = (3k+6)/(k-2)
User Mitaka
by
5.1k points